(untitled) (Global Journal of Management and Business Research, 1970)
The foreign restaurant industry is now entering Bangladesh as people are heading toward restaurants with their families and friends Domino s Pizza Bangladesh started its journey in March 2019 It has attracted many customers So many factors contribute to attracting and retaining customers in this type of service industry This chain of restaurants researched Bangladesh to find the potential of their business here As soon as they find it feasible they start their journey here However there is very little research on the factors that can contribute to the satisfaction of customers So the researchers conducted the research to identify the factors that contribute to the satisfaction of the customers of Domino s Pizza It is mainly quantitative research and both primary and secondary data were collected A survey questionnaire was made on Google Forms and collected responses from 103 respondents online 51 were female and 52 were male respondents among the 103 respondents